IMPLEMENTASI PENDIDIKAN NILAI MELALUI PERMAINAN TRADISIONAL ANAK SUKU SASAK DI MI NW LOANG SAWAK LOMBOK TENGAH - Zainal Arifin Munir; Awiria Awiria (Universitas Sarjanawiyata Tamansiswa, 2020)
Traditional games of a tribe had often not been known well in the last few decades, traditional games had been shifted to the digital ones that were imported from around the world. This study aimed at finding out how to implement educational values through the traditional game of the Sasak tribe in MI NW Loangawak, Mataram was. The method used was descriptive qualitative analysis. The subjects of this study were students, teachers, and school principals. Data collection techniques used were interviews, observation, and documentation. To check the validity of the data, researchers used data triangulation techniques. The results showed that the implementation of educational values through traditional games was excellent, because traditional games substantially contained and were closely related to natural elements, both in terms of playgrounds, as well as playing tools used in traditional games, such as wooden sticks as raw material for gasing. It played an essential role in bringing people closer to their natural world and bringing a deeper understanding of the place, which they had made for dwellings, as ecological knowledge that was not only considered as a science and harmony of fellow human beings, but also as the soul of life.